GENDER VIOLENCE AND JURY COURT: feminicide and the (im)possibility of a new trial in the face of a decision manifestly contrary to the evidence in the case: (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article proposes to discuss the possibility of a new trial in the face of an absolute decision that is manifestly contrary to the evidence in the file in cases of femicide, considering the commitment of the Brazilian State to protect women's rights assumed through international Conventions. Brief considerations are made about the system of the jury, the violations of the human rights of the women present during femicide trials, as well as an analysis of the use of the principle of sovereignty of verdicts as an obstacle to the holding of a new jury, and its implications in the effective exercise and protection of women's rights. The method used was a bibliographic and qualitative review, without prejudice to specific quantitative analyses, as the objective is not to discuss the correctness or incorrectness of judicial decisions, but rather to identify guidelines and the possibility of making the Jury Court's premises compatible with the commitment assumed by the Brazilian State to protect and promote gender equality.